2006
DOI: 10.1088/0953-8984/18/3/021
|View full text |Cite
|
Sign up to set email alerts
|

Oxide muonics: I. Modelling the electrical activity of hydrogen in semiconducting oxides

Abstract: A shallow-to-deep instability of hydrogen defect centres in narrow-gap oxide semiconductors is revealed by a study of the electronic structure and electrical activity of their muonium counterparts, a methodology that we term ‘muonics’. In CdO, Ag2O and Cu2O, paramagnetic muonium centres show varying degrees of delocalization of the singly occupied orbital, their hyperfine constants spanning 4 orders of magnitude. PbO and RuO2, on the other hand, show only electronically diamagnetic muon states, mimicking thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 50 publications
5
42
0
Order By: Relevance
“…Several subsequent µSR studies have revealed the shallow donor-nature of muonium in the TCO materials In 2 O 3 and SnO 2 [102], CdO [103], and Ga 2 O 3 [104] (see, for example, Fig. 6).…”
Section: Universality Across Tcosmentioning
confidence: 99%
“…Several subsequent µSR studies have revealed the shallow donor-nature of muonium in the TCO materials In 2 O 3 and SnO 2 [102], CdO [103], and Ga 2 O 3 [104] (see, for example, Fig. 6).…”
Section: Universality Across Tcosmentioning
confidence: 99%
“…18,19 The short lifetime (2.2 μs) of the implanted positive muonium is reflected on the short time-scale measurements performed under nonequilibrium conditions and allows the observation of the isolated defect centers that are responsible for the electrical activity of hydrogen. 17,20,21 Although the muon is only one ninth the mass of the proton, the reduced mass of muonium is 99.6% of that of hydrogen, so that the respective electronic properties are basically the same in both atoms. 20 μSR spectroscopy has also the advantage of being sensitive to both neutral (paramagnetic) and charged (electronically diamagnetic) states of muonium and of being able to distinguish deep 22 and shallow centers.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,21 Although the muon is only one ninth the mass of the proton, the reduced mass of muonium is 99.6% of that of hydrogen, so that the respective electronic properties are basically the same in both atoms. 20 μSR spectroscopy has also the advantage of being sensitive to both neutral (paramagnetic) and charged (electronically diamagnetic) states of muonium and of being able to distinguish deep 22 and shallow centers. 16,23 Thus, extensive studies have already been carried out to verify whether deep muonium (resembling the atom-like localized state of hydrogen) or shallow-donor muonium are formed in different semiconductors and oxides, hence providing a reasonably good comparison to whether hydrogen behaves as a deep or shallow impurity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Similar to the situation in ZnO, hydrogen recently has been proposed to be an important n-type dopant in several transparent conducting oxides. [4][5][6][15][16][17][18] SnO 2 is a prototypical transparent conducting oxide. 11,12,19 Recent theory finds that native defects are unlikely to be the source of conductivity.…”
Section: Introductionmentioning
confidence: 99%